2016
DOI: 10.1016/j.jhazmat.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of akageneite (beta-FeOOH)/reduced graphene oxide nanocomposites for oxidative decomposition of 2-chlorophenol by Fenton-like reaction

Abstract: h i g h l i g h t s• Ak/rGO was successfully prepared by co-precipitating and reduction processes.• Fe O C band inhabited the reduction of graphene oxide.• Degradation rate of 2-chlorophenol for Ak/rGO increased 2-5 times than that for Ak.• Higher removal rate is due to the syn- In this work, the composite of reduced graphene oxide and akageneite (Ak/rGO) was synthesised by co-precipitating and reduction processes. The morphological and structural features of the synthesized composites (Ak/rGO) were characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…10 To overcome these negative effects, recyclable heterogeneous catalysts like metal oxides, hydroxides and suldes have been used to replace homogeneous catalysts. [11][12][13][14][15][16] Since then, enormous progress has been made in heterogeneous catalysis; however, most catalysts still show stability issues at certain values of pH, particularly under strong alkaline conditions. Hence, it is necessary to prepare other types of catalysts with a high catalytic activity and a wide applicable pH range.…”
Section: Introductionmentioning
confidence: 99%
“…10 To overcome these negative effects, recyclable heterogeneous catalysts like metal oxides, hydroxides and suldes have been used to replace homogeneous catalysts. [11][12][13][14][15][16] Since then, enormous progress has been made in heterogeneous catalysis; however, most catalysts still show stability issues at certain values of pH, particularly under strong alkaline conditions. Hence, it is necessary to prepare other types of catalysts with a high catalytic activity and a wide applicable pH range.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray diffraction patterns ( Figure S1) did not show any specific diffraction peaks of Fe oxides, which could be explained by the high dispersity of the Fe oxides particles and the relatively low Fe loading content (around 1.5% determined by ICP-9000) [22]. The XPS (X-ray photoelectron spectroscopy) spectra of Fe@CC were shown in Figure 1.…”
Section: Characterization Of Catalystsmentioning
confidence: 97%
“…Similarly, the peak that appeared at 1383 cm -1 to 1449 cm -1 was a methylene stretching that linked to the C−C groups in the BCs. The FTIR results revealed that the different BCs had different functional groups, which could be attributed to the biochar species (Xiao et al 2016). The biochar properties considerably affect the interactions between 2,4-DCP and the functional groups during the sorption process (Cui et al 2016).…”
Section: Ftir Of Bcsmentioning
confidence: 99%
“…It is extensively used to control insects and weeds globally (Peng et al 2016). The excessive use of chlorophenols leads to the pollution of surface water, underground water, air, and agricultural fields (Shih et al 2012;Xiao et al 2016). Vlastos et al (2016) reported that 2-chlorophenol (only one Cl element) with the concentrations up to 1 μg mL -1 could cause chronic toxicity to microbes and fish.…”
Section: Introductionmentioning
confidence: 99%